Bifidobacterium animalis ssp. lactis 420 Protects against Indomethacin-Induced Gastric Permeability in Rats - Anna Lyra; Markku Saarinen; Heli Putaala; Kaisa Olli; Sampo J. Lahtinen; Arthur C. Ouwehand; Mari Madetoja; Kirsti Tiihonen (Gastroenterology Research and Practice)
Gastrointestinal (GI) adverse effects such as erosion and increased permeability are common during the use of nonsteroidal anti-inflammatory drugs (NSAIDs). Our objective was to assess whether Bifidobacterium animalis ssp. lactis 420 protects against NSAID-induced GI side effects in a rat model. A total of 120 male Wistar rats were allocated into groups designated as control, NSAID, and probiotic. The NSAID and probiotic groups were challenged with indomethacin (10 mg/kg−1; single dose). The probiotic group was also supplemented daily with 1010 CFU of B. lactis 420 for seven days prior to the indomethacin administration. The control group rats received no indomethacin or probiotic. The permeability of the rat intestine was analysed using carbohydrate probes and the visual damage of the rat stomach mucosa was graded according to severity. B. lactis 420 significantly reduced the indomethacin-induced increase in stomach permeability. However, the protective effect on the visual mucosal damage was not significant. The incidence of severe NSAID-induced lesions was, nevertheless, reduced from 50% to 33% with the probiotic treatment. To conclude, the B. lactis 420 supplementation protected the rats from an NSAID-induced increase in stomach permeability and may reduce the formation of more serious GI mucosal damage and/or enhance the recovery rate of the stomach mucosa.